Understanding reciprocity in human–robot interactions through completion of a pregiving favor - Moberg, Reilly; Downs, Edward; Shelby, Abby; Khan, Arshia (Smart health (Amsterdam), 2024)
In today’s world, understanding how people interact with humanoid social robots is important for day-to-day interactions and design purposes. A phasic, between-subjects, psychophysiological experiment (N = 72) examined how the norm of reciprocity influenced interactions with the humanoid social robot, “Pepper”. Facial electromyography (zygomatic and corrugator) was measured to determine participant’s emotional valence during interaction. The level of reciprocity in response to a pregiving favor was measured by the number of raffle tickets purchased by participants at the robot’s request. Results suggest that the social rule of reciprocation exists within human–robot interaction. When Pepper offered a pregiving favor to a participant, that person was more likely to reciprocate via the robot’s later ticket purchase request. Contributions to theory and design of humanoid social robots are discussed, as well as avenues for future research.